Introduction of New Stress-Resistant and High-Yielding Winter Wheat Varieties Based on Chromosome Engineering and Marker-Assisted Selection - Morgun, V.V.; Gavrilyuk, M.M.; Oksem, V.P.; Morgun, B.V.; Pochynok, V.M. (Science and Innovation, 2024)
The results of research conducted in 2013 at the Institute of Plant Physiology and Genetics of NASU have been showed. The status of soft winter wheat breeding, seed production, and varietal resources of strategic culture has been identified. The examples of how the crop areas of innovative varieties significantly expanded within the territory of Ukraine and how the innovative varieties started being produced in nearby countries have been described.